PTH-070 Correlation of the recorded image quality index (RIQI) score with existing colonoscopy key performance indicators. (8th June 2018) - Edwards, Kate; Berrill, James; Hurley, Joanna; Lee, Bee; Hawkes, Neil
Abstract : Introduction: The RIQI score (scale 0–10) has been validated as a measure of the quality of image recording during endoscopic examination. A high RIQI score (9–10) provides good clinical utility of the images to support clinical decision-making e.g. in MDTs. Taking high quality images requires good tip control to hold the correct focal length and time spent cleaning the mucosa. We aimed to assess the correlation between median RIQI scores and existing colonoscopy key performance indicators (KPIs) including the Caecal Intubation Rate (CIR), Polyp Detection Rate (PDR) and median colonoscopic withdrawal time (WDT). Methods: 80 datasets of clinical images were reviewed by 3 assessors yielding a median RIQI score from 30 observations for 8 independently practising colonoscopists. This was correlated against annual KPI data for each colonoscopist – including CIR (%), PDR (%) and median WDT (mins). Pearson Rank correlation was performed. Results: Median RIQI scores for the 8 colonoscopists ranged from 2 to 10 (<5= poor; 6–8=moderate, 9–10=high image quality). Unadjusted CIR ranged from 81.6% to 95.0%; PDR from 24.2% to 64.5% and median WDT from 7 to 19 min. Median RIQI scores had a moderate to good positive correlation with existing KPIs – correlation values: CIR r=0.59; PDR r=0.53; WDT=0.54. Conclusions: The RIQI score is a novel KPI assessing the recording of image quality. This is a surrogate marker of both tip control and ability to identify, wash and assess lesions. We have demonstrated that the RIQI score shows positive correlation with other commonly used KPIs in colonoscopy and further work is anticipated in exploring its role in upper GI endoscopy aligned to the BSG Quality Standards. 1 Reference: 1. Beg S, Ragunath K, Wyman A, et al. Quality standards in upper gastrointestinal endoscopy: a position statement of the British Society of Gastroenterology (BSG) and Association of Upper Gastrointestinal Surgeons of Great Britain and Ireland (AUGIS). Gut 2017 Sep 13:gutjnl-2017.